(untitled) (Journal of Dhaka National Medical College & Hospital, 2015)
Bacterial infections are a major cause of illness in patients with hematological malignancy and can lead to mortality, if not treated early and properly. The incidence of bacterial infection in these patients and the spectrum of causative organisms are liable to change according to region & time. This observational study was designed to isolate and identify the aerobic bacteria causing infection in patients with hematological malignancy. The Study was done in the Department of Microbiology and Immunology, BSMMU from March 2012 to August 2012. Forty diagnosed patients of hematological malignancies who were admitted in the Hematology Department and in The Paediatric Hemato-oncology Department of BSMMU with symptoms of sepsis &/ or UTI or RTI were enrolled in this study. Blood, throat swab and urine were collected from each patient and sputum was collected from four patients. Infection was microbiologically detected in 37.5% of patients. Gram negative bacteria were most frequently isolated from various specimens except throat swab from which only S. pyogenes were isolated. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 3-5